امام شاطبی کے بدعت کے موقف کا تحقیقی مطالعہ: A CRITICAL STUDY OF IMAM SHATIBI’S VIEW OF BIDAH (REPREHENSIBLE INNOVATION) (Zia e Tahqeeq, 2025)
The Quran and Sunnah of the Prophet Muhammad (peace be upon him) guide Muslims how to live and interact with each other in all spheres of life. Both dogma and practices are completed described. Muslims are advised to follow the tradition of the Prophet Muhammad and his companions. Therefore, the ideas or practices which are contrary to the Prophetic traditions are prohibited. The matters which are not in the tradition are bidah (innovations) and not recommended for practice. According to the lexical meaning, every new work whether it is good or bad, righteous or corrupt is said to be innovation. For this reason, the Islamic scholars have divided innovation. That’s why without any discrimination innovation is considered as one unit and every new work that is invented after the era of the Prophet Muhammad and His followers, is not declared in disgrace, haram and misguidance. Imam Shatibi is one of the scholars who evaluated the concept of Bidah and elaborated its various forms and levels.